Rainfall and Topography in Eastern and Southern Africa:Statistical and Geostatistical Modelling - (:unkn) unknown (My University, 2008)
By considering two examples in Eastern and Southern Africa, this work has two aims: a better understanding of the influence of topography on the spatial distribution of rainfall and an optimal interpolation of station rainfall data, taking into account topography. To this end, an original methodology is developped, partly derived from previous studies focusing on extratropical regions. First, a statistical model is defined. With the help of a multi-scalar decomposition of topographical information into descriptors, a multiple linear regression is performed. This model is used to better understand the relationship between rainfall and topography. In Eastern Africa, the spatial distribution of rainfall depends on aspect and summit/ridge locations. In Southern Africa, the most important factor is a rainfall gradient from south-west to north-east, which almost smoothes out the influence of topography. The importance of the rainfall gradient decreases in the end of rainfall season. Second, the errors of statistical modelling are interpolated with the help of geostatistical modelling. The result is a multiplicative model, used to reconstitute monthly mean rainfall fields, for each region. The corresponding maps demonstrate the capacity of the model to reproduce spatial variability of mean rainfall, especially in Eastern Africa. Third, the interannual evolution of the relationship between monthly rainfall and topography is analysed. From year to year, the rainfall models explain an uneven part of spatial distribution. An original methodology is used to determine if there are recurrent patterns of rainfall (modes) related to the same topographical descriptors. In Eastern Africa, only the transition months between rainy and dry seasons show significant results. The associated modes are connected to recurrent anomalies in large-scale atmospheric circulation. The most important results are linked to the ons
Keywords: African Research